SYNTHESIS AND CHARACTERIZATION OF THERMO SENSITIVE POLYMER PNIPA FOR THERAPEUTIC RADIATION SOURCE - Rohadi Awaludin; Herlina Herlina (Widyariset, 2011)
Synthesis of poly(N-isopropylacrylamide) (PNIPA) by free radical polymerization has been carried out. NIPA monomer was polymerized by free radical polymerization with the initiator of ammonium persulfate (APS) and tetramethylethylenediamine (TEMED). The purpose was to obtain PNIPA for the base-material of therapeutic radiation source.  Visual observations indicated that the polymer solution showed different properties at 35ºC. FTIR spectrum showed that infrared absorption peaks of the synthesized polymer were almost the same as PNIPA reported before. Viscosity measurement showed that there was a change of viscosity at temperatures of 30–35ºC. Viscosity of the solution increased dramatically with the increase of concentration. The maximum concentration of the polymer solution for radiation source was 5%.